Pipe Insulation Evaluation for Low-Temperature District Heating Implementation in South Korea - Usman, Muhammad; Kim, Yong Ki (Frontiers in Energy Research, 2022)
Future energy systems will comprise 100% renewable energy and involve high integration of energy systems. District heating (DH) and cooling systems will be an undeniable part of future energy systems, as they facilitate high-efficiency, low-cost, and clean production. Low-temperature district heating (LTDH) is one of the candidates for future district heating systems, where the supply temperature is 60 °C or below. Reducing heat losses from the pipe network in DH systems is challenging. Improving the insulation standards in DH pipes can decrease heat and temperature losses in the pipe networks. This study employs computational fluid dynamics to evaluate the optimum insulation thickness based on the material and digging costs in South Korea. An evaluation of a micro DH system with a 500 m pipe network system supplying hot water at 60 °C with polyethylene, ethylene propylene diene monomer rubber, and polyurethane as insulation materials using ANSYS Fluent 17.2 shows that the heat losses are minimal when using PU foams. A cost estimation analysis showed that 32 mm was the optimum insulation thickness for achieving heat losses below 20 W/m and minimum material and digging costs when burring the pipeline network in the ground.